ANALYSIS OF STUDENT’S MATHEMATICAL REASONING ABILITY IN LEARNING INDEPENDENCE ON GEOMETRY MATERIALS - ANDIRA RAHMAWATI; AYU TSURAYYA (FKIP Universitas Muhammadiyah Tangerang, 2023)
One of the standards of competence included in the default development process is the ability to reason, which is one of the skills to be developed. In resolving potentially challenging problems, students need to develop the ability of a student's mathematical reasoning. It is, therefore essential to improve students' mathematical reasoning ability. The purpose of this study is to describe how junior high students use mathematical reasoning to solve geometry problems with their learning independence. This study used a descriptive qualitative research methodology using 30 class VIII junior high school students in Bekasi as research subjects. The methods used to obtain information include written tests for mathematical reasoning abilities, independent learning questionnaires, and interviews to find out whether the answers given are correct as they are and to strengthen the results of the previous written test. The results showed that students with the highest mathematical reasoning abilities also had a high level of learning independence from all subjects in this study. However, students who have not fully met the indicators of mathematical reasoning ability have good learning independence.